Red phosphorus embedded in TiO2/C nanofibers to enhance the potassium-ion storage performance. Issue 13 (29th March 2021) - Su, Die; Dai, Jing; Yang, Min; Wen, Jiaxing; Yang, Jianping; Liu, Wen; Hu, Hai; Liu, Li; Feng, Yan
Abstract : TiO2 -RP/CN was fabricated and found to possess a special structure and an excellent electronic conductivity, and the electrodes show outstanding energy storage in K half/full cells. Abstract : TiO2 -red phosphorus/C nanofibers (TiO2 -RP/CN) have been synthesized via electrospinning and then annealed with red phosphorus sublimation. Benefiting from the high electronic/ionic conductivity and robust stability of the unique structure, the TiO2 -RP/CN show high reversible capacities, as well as an outstanding cycling ability. In K half cells, the capacity decay of the TiO2 -RP/CN electrode mainly occurs in the first few cycles, and at 0.05 A g −1 it delivers a high specific capacity of 257.8 mA h g −1 after 500 cycles. K full cells were fabricated; these are well-matched with PTCDA (perylene-3, 4, 9, 10-tetracarboxylic dianhydride) and also exhibited a good electrochemical performance (62 mA h g −1 after 100 cycles). Therefore, the TiO2 -RP/CN are potential anode materials for use in K-ion batteries.